PORTRAIT STUDENTS' SELF-DISCLOSURE IN JUNIOR HIGH SCHOOLS PONTIANAK CITY - Halida, Halida; Wicaksono, Luhur; Syawaluddin, Syawaluddin; Sendayu, Fendahapsari Singgih; Dharmayanti, Putu Ari (Universitas Tanjungpura, 2024)
This research aims to provide an overview of the self-disclosure of junior high school students in the city of Pontianak. The sample was 520 students, sampling used random sampling. Data collection, using a self-disclosure questionnaire, was given to students using Google forms. The method used is a descriptive method, with descriptive statistical analysis. There are five indicators studied, namely: self-disclosure in socializing, dressing, determining the future, managing finances and self-disclosure in personality. The research results stated that students' self-disclosure was in the sufficient category. Based on gender, women have the highest average self-disclosure compared to men. Self-disclosure regarding the future and personality is in the high category. Meanwhile, indicators of self-disclosure in socializing, dressing and managing finances are in the medium category. It is hoped that future research can carry out relational research to see the relationship between self-disclosure and parental parenting patterns, local cultural values and socio-economic status.Keywords: Middle school student, Self-disclosure, Portrait